1998
DOI: 10.1002/(sici)1097-4628(19981128)70:9<1649::aid-app2>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy/castor oil graft interpenetrating polymer networks

Abstract: Full-interpenetrating polymer networks (IPNs) were prepared from epoxy and castor oil-based polyurethane (PU), by the sequential mode of synthesis and were characterized by different techniques: swelling test, scanning electron microscopy (SEM), thermomechanical analysis (TMA), thermogravimetric analysis (TGA), tensile test, and instrumented impact test. 2,4-Toluene diisocyanate (TDI) was used as a curing agent for castor oil, at a NO/OH ratio ϭ 1.50. Diglycidyl ether of bisphenol A (DGEBA) was cured and cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 15 publications
2
50
0
1
Order By: Relevance
“…Instead of giving much effort to give change in the chemistry of polymer structures, the way of mixing of one polymer alloy with another alloy shows the increase in all aspects of mechanical property. This IPN system shows excellent property than the Individual (single) components, as well the individual specific characteristics of the polymer are extracted in such a way to achieve or meet our the requirement of the present day industries [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of giving much effort to give change in the chemistry of polymer structures, the way of mixing of one polymer alloy with another alloy shows the increase in all aspects of mechanical property. This IPN system shows excellent property than the Individual (single) components, as well the individual specific characteristics of the polymer are extracted in such a way to achieve or meet our the requirement of the present day industries [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethanes based on CO with different diisocyanates seem to be interesting alternatives to non-renewable-based materials, in agreement with the concept of sustainable development. There are several reports related to the elaboration of polyurethanes, such as IPNs [9,10] cast elastomers [8,11] and polyurethane coatings. [12] Different characterizations and analysis have been carried out on these systems.…”
Section: Introductionmentioning
confidence: 99%
“…A weighed amount of castor oil was placed in a roundbottomed flask, thoroughly mixed with a predetermined amount of TDI at 65°C, which corresponds to a fixed NCO/OH ratio of 1.50 [15]. The system was stirred vigorously with mechanical stirring, under an atmosphere of dry nitrogen, for about 45 min to form a PU prepolymer.…”
Section: Preparation Of Pu/ep Ipn and Htpdms Modified Ipn Compositesmentioning
confidence: 99%
“…To further improve the performance of PU/EP IPNs, much attention has been paid to modifying them. Studies have shown that the PU/ EP IPN composites had rather high mechanical strength, high damping properties, and good thermal stability [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%